Gateway Deployment Optimization in Wireless Mesh Backbone Network Based on Closeness Centrality - Chengxin Guo; Taoshen Li; Zhihui Ge (Dianxin kexue)
Directional antenna and Delaunay graph were used in the gateway deployment optimization of wireless mesh backbone network and a gateway deployment optimization algorithm of wireless mesh backbone network based on closeness centrality was proposed. Firstly, according to the largest traffic of mesh router and gateway, the algorithm divides the network into a few clusters forming Delaunay sub-graph. In the sub-graph, according to the Euclidean distance of each nodes to the center nodes, the algorithm find out the closest three nodes to the center nodes and form the gateway candidate set. The node in this gateway candidate set, which has the shortest route path to the other nodes, is the location of gateway of this cluster. Gateway location of each sub-graph will be achieved in the end. Simulation experimental results show that, after reasonable network partitioning according to the largest traffic of gateway, the algorithm can minimize the number of network gateway. The total path length from the mesh routers to the gateway of the algorithm is better than that of the random algorithm.